2021
DOI: 10.1088/1748-9326/abd130
|View full text |Cite
|
Sign up to set email alerts
|

Project Coolbit: can your watch predict heat stress and thermal comfort sensation?

Abstract: Global climate is changing as a result of anthropogenic warming, leading to higher daily excursions of temperature in cities. Such elevated temperatures have great implications on human thermal comfort and heat stress, which should be closely monitored. Current methods for heat exposure assessments (surveys, microclimate measurements, and laboratory experiments), however, present several limitations: measurements are scattered in time and space and data gathered on outdoor thermal stress and comfort often does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Physical exercise provides mental health benefits and reduces the risk of cardiovascular disease, diabetes, cancer, cognitive decline, and all-cause mortality. [69][70][71][72][73] However, high temperatures can reduce the frequency of physical activity, duration of physical activity, and the desire to engage in exercise, [74][75][76] and even low amounts of physical activity in high temperatures can pose a risk to health. 77 This indicator estimates the loss of potential hours of safe physical activity per person due to ambient temperature, humidity, and radiant heat, by tracking the hours per day that the wet bulb globe temperature exceeds 28°C, a threshold above which the national sports medicine authorities of the USA, Australia, and Japan recommend outdoor physical activities are done with discretion.…”
Section: Section 1: Climate Change Impacts Exposures and Vulnerabilitymentioning
confidence: 99%
“…Physical exercise provides mental health benefits and reduces the risk of cardiovascular disease, diabetes, cancer, cognitive decline, and all-cause mortality. [69][70][71][72][73] However, high temperatures can reduce the frequency of physical activity, duration of physical activity, and the desire to engage in exercise, [74][75][76] and even low amounts of physical activity in high temperatures can pose a risk to health. 77 This indicator estimates the loss of potential hours of safe physical activity per person due to ambient temperature, humidity, and radiant heat, by tracking the hours per day that the wet bulb globe temperature exceeds 28°C, a threshold above which the national sports medicine authorities of the USA, Australia, and Japan recommend outdoor physical activities are done with discretion.…”
Section: Section 1: Climate Change Impacts Exposures and Vulnerabilitymentioning
confidence: 99%
“…In recent years, the collection and utilisation of vast amounts of data via crowdsourcing, i.e., the collection of data from nontraditional sources via the internet (Muller et al, 2015), has gained much attention. Such non-traditional, opportunistic sources of data are, e.g., smartphones (e.g., Overeem et al, 2013b;Mass and Madaus 2014;Droste et al, 2017), smart wearable devices (Nazarian et al, 2021), cars (e.g., Haberlandt and Sester 2010;Bartos et al, 2019), commercial microwave links (e.g., Messer et al, 2006;Overeem et al, 2013a;Chwala and Kunstmann 2019), and privately-owned weather stations, called citizen weather stations (CWS) in the following (e.g., Steeneveld et al, 2011;Wolters and Brandsma 2012;Bell et al, 2013;Madaus et al, 2014;Chapman et al, 2017;de Vos et al, 2017;Venter et al, 2021). Each type of these data sources alone or multiple combined can be used in different meteorological and climatological applications, such as weather forecast (e.g., Mass and Madaus, 2014;Nipen et al, 2020), operational weather monitoring (e.g., de Vos et al, 2019), mesoscale model evaluation (e.g., Hammerberg et al, 2018), hydrometeorological analyses and modelling (e.g., Smiatek et al, 2017;de Vos et al, 2020), high-resolution mapping of air temperature (e.g., Venter et al, 2020;Vulova et al, 2020;Zumwald et al, 2021), thermal-comfort assessment (Nazarian et al, 2021), and urban climate investigations (e.g., Fenner et al, 2017Fenner et al, , 2019Droste et al, 2020;Feichtinger et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of nontraditional and opportunisticsensing technologies in meteorological and climatological research, such as smartphones (Overeem et al, 2013b;Mass and Madaus, 2014;Droste et al, 2017), cars (Haberlandt and Sester, 2010;Mahoney and O'Sullivan, 2013;Bartos et al, 2019), commercial microwave links (Messer et al, 2006;Zinevich et al, 2009;Overeem et al, 2013a;Chwala and Kunstmann, 2019), wrist-mounted wearables (Nazarian et al, 2020), and privately owned citizen weather stations (CWSs), e.g., Wolters and Brandsma (2012), Bell et al (2015), de Vos et al (2017, Meier et al (2017), Fenner et al (2019, Droste et al (2020), and Mandement and Caumont (2020), have shown to provide additional and reliable information, thus, highlighting a multitude of possible applications in research and beyond (de Vos et al, 2019;Nipen et al, 2020). To study urban air temperatures and the UHI effect, data from CWSs have been used in a variety of studies (Steeneveld et al, 2011;Chapman et al, 2017;Fenner et al, 2017;de Vos et al, 2020;Feichtinger et al, 2020;Venter et al, 2020;Vulova et al, 2020), focusing on different cities.…”
Section: Introductionmentioning
confidence: 99%